PEMERINTAH DESA DAN PENGELOLAAN DANA DESA UNTUK MENCIPTAKAN KESEJAHTERAAN MASYARAKAT DESA LAWAHING, KECAMATAN KABOLA, KABUPATEN ALOR - Lapenangga, Loudric J. P.; Stefanus, Kotan Y; Lamantaro, Cyrilus W. T (Petitum Law Journal, 2023)
Village is a legal community unit that has territorial boundaries that are authorized to regulate and manage government affairs, the existence of the Village juridically in Law Number 6 of 2014 concerning Villages explained that the Village is the smallest part of the government administration system. Village funds are a follow-up to the government's program to build Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state that aims to improve welfare and equitable development through improving public services, advancing the economy, overcoming development gaps between villages and strengthening communities as subjects of development. From the description above, the author is interested in conducting research using criminological theories, with the following problem formulation: 1) What is the function of the village government in managing village funds? 2) What is the impact of village fund management on the welfare of the people of Lawahing Kabola Village, Alor Regency? Research Methods is empirical juridical research. Research results The results showed that: Management Village funds carried out by Lawahing Village are good enough with various activities including for the welfare of the village community but want the Lawahing Village community apparatus to be more active in planning, implementing and evaluating village community empowerment work programs in order to improve the welfare of the village community and for Lawahing Village officials to be more active in planning, implementing and evaluating village community empowerment work programs in order to improve the welfare of the village community.